A multibody dynamics model to assess the impact of road unevenness on the efficiency of a semitrailer truck. (19th February 2015) - Gagnon, Louis; Richard, Marc J.; Doré, Guy
An open source multibody model of a semi-trailer truck with 331 degrees of freedom was built and within it a dynamic tyre model has been implemented. The truck model was calibrated and validated by an on-road experimental campaign of coastdown tests. The signal from a photodetector and ten accelerometers, the weight distribution, meteorological data, and the longitudinal profile have been collected. The purpose of the model is to obtain the relationships between the longitudinal road profile and fuel consumption, vehicle wear, passenger health, and safety. A subsequent study demonstrated the capacity of the model to fulfil its purpose.